Mandibular angle fracture due impacted third molar inclusion: case report - Gaetti Jardim, Ellen Cristina; Pereira, Cassiano Costa Silva; Garcia Junior, Idelmo Rangel; Gaetti-Jardim Junior, Elerson; Leite da Silva, Julio Cesar (ARCHIVES OF HEALTH INVESTIGATION, 2016)
Mandibular angle region is enshrined in literature as a fragile area because of the third molar presence further when its impaction shaping up as a rare complication associated with more attempts to extraction of the tooth. Several factors influence the possibility of fracture as gender, age, degree of dental inclusion and presence of associated injuries. The best form of treatment depending on the case is surgical, consisting of placing the intraosseous fixing devices. The purpose of facilitated and a conservative approach for the treatment of fractures of mandibular angle is displayed. Also, demystify the contraindication of intraoral access for cases of unfavorable fractures to displacement. This study, in addition, been reports two clinical cases of mandibular angle fractures in the presence of a third included molar treated by means of intraoral access set by Champy technique of external oblique line with the use of single board in office dental. Results: This approach is well suited to cases with little displacement of the fracture line and when the patient shows collaborator. This technique as well as fast, reduces spending on hospital besides reducing postoperative sequelae because it prevents the need for extra-oral access. Descriptors: Fracture Fixation; Therapeutics; Anesthesia, Local; Molar, Third.